Computational and experimental analysis of high gain antenna for WLAN/WiMAX applications - Ahsan, M.R.; Islam, M.T.; Ullah, M.H. (2015)
In this paper a new microstrip-fed planar triple-band antenna has been proposed which is applicable for wireless communication standards WLAN/WiMAX applications. The proposed antenna is composed of radiating patch loaded with open square-loop and arc slots and rectangular full length ground plane with defect on it. The geometry of the designed antenna has been parametrically analyzed and optimal dimensions are obtained through numerical computations by using a commercial electromagnetic field simulator. On the basis of conceptual design, a physical module of the antenna has been realized on ceramic filled polytetrafluoroethylene based dielectric substrate of and loss tangent, . The measurement results from the antenna prototype show dB impedance bandwidths of 630 MHz (2.16-2.79 GHz), 600 MHz (3.27-3.87 GHz) and 690 MHz (5.28-5.97 GHz) which can simultaneously cover the bandwidth requirements for all WLAN/WiMAX standards. The designed antenna exhibits nearly symmetric and omnidirectional radiations patterns over the three operating bands. The antenna prototype has shown maximum radiation gains at the frequency bands of 2.49, 3.54 and 5.6 GHz are about 5.71, 6.16, and 6.48 dBi. The experimental results are in good agreement with the results obtained from numerical computation and the designed antenna can be a good candidate for multiband operations in 2.4/5.2/5.8 GHz WLAN and 2.5/3.5/5.5 GHz WiMAX standard wireless applications.